Optimizing IT Service Performance Through COBIT 2019-Based Governance Design at Keling Kumang Institute of Technology - Angela AL; Alva Hendi Muhammadi (Sebatik, 2026)
The Keling Kumang Institute of Technology (ITKK) is a new university in Sekadau Regency, West Kalimantan, which faces challenges in IT management to support academic and managerial operations, including delays in IS and IT infrastructure maintenance, power and internet disruptions, a lack of competent IT human resources , and limited budget and network infrastructure. The complexity of IT services such as SIAKAD, Server and Network Systems, and OJS, requires the implementation of structured IT governance so that IT services run optimally and in line with the institution's vision and mission . This study aims to find weaknesses in IT governance through an analysis of current IT capabilities (as-is) and expected conditions (to-be), as well as to develop recommendations to achieve good governance levels. This study was conducted using the COBIT 2019 framework with 4 process objective domains that have been identified through consultation with ITKK stakeholders and stakeholders, namely APO04, APO07, DSS05, and BAI06. Based on the gap analysis, APO04 has evidence work of product at the Largely Achieved level (50-84%), APO07 has significant challenges in IT HR management with a Not Achieved value (0-49%) at Level 1, DSS05 shows weaknesses in network and endpoint security aspects with a Partially Achieved value (15-49%) at Level 2, and BAI06 requires substantial improvements in IT change management with a Partially Achieved value (15-49%) at all levels. The recommendations provided include the preparation of IT governance policies that are integrated with the ITKK Strategic Plan and VMTS, improving IT HR competency through training and certification, strengthening network security infrastructure, and implementing documented IT change management procedures